Seasonal Variations in the Age-Related Biometrical Studies on the Ovary of Local Sheep (Ovis aries) under Temperate Agro-climatic Conditions of Kashmir Valley - Ahmad, Mir Shabir; Khan, Massarat; Choudhury, A. R.; Pampori, Z.A; Dar, F. A.; John, M.A.; Andleeeb, R.; Shah, S.A.; Dar, S. H. (Indian Journal of Veterinary Anatomy, 2023)
The ovaries from 78 non-descript ewes of Kashmiri region of prepubertal, pubertal and adult groups were collected in different seasons. As the age increases the length, breadth, thickness and weight of the ovary increased significantly and was found to be maximum in adult groups and least in prepubertal groups. The values oflength were significantly higher (p < 0.05) during Autumn among the different seasons. The average breadth and thickness was found to be non-significantly higher (p > 0.05) in Autumn and Winter season respectively. Most of the parameters observed were higher on right ovary yet difference was not significant (p > 0.05). The weight of right ovary was significantly higher (P < 0.05) in Autumn whereas it was significantly higher (P < 0.05) in spring season for the left ovary. Ovaries of both sides showed seasonal variation in their gross morphology. They were highly active during autumn season as demonstrated by their increased overall size and number of mature/maturing follicles on the surface. Conversely during summer season the length, breadth and thickness measured the least. The right ovary was generally larger and presented more follicles than the left ovary. The average follicles recorded on left ovary was 9.02 and 11.27 on right ovary.